Representasi sensualitas simbolis pada iklan alat kontrasepsi: (Analisis Semiotika Roland Barthes) - Afrisyah, Misbahul; Kurniawan, Bima (CV. Kurnia Grup, 2024)
This study aims to examine the symbolic representation of sensuality in contraceptive advertisements, specifically the